Proposal of a new servo-motor optimized for educational robotic applications - Silva, João (2018)
This paper describes the development of SMORA (Servo Motor Optimised for Robotic Applications), which consists of custom hardware and firmware that includes a microcontroller and a series of sensors, allowing for the motor current, temperature and voltage to be measured in real-time as well as precise position feedback thanks to the integrated hall-effect magnetic position encoder. It also incorporates an accelerometer and a gyroscope to measure the servo body relative position and rotation.